Seasonal Changes and Regulation of the Glucocorticoid Receptor in the Testis of the Toad Rhinella arenarum - Regueira, Eleonora (2012)
Several studies indicate that wild free‐living vertebrates seasonally regulate plasma glucocorticoids. However, not only glucocorticoids but also the amount of receptors is important in determining biological responses. In this context, seasonal regulation of glucocorticoid receptor (GR) is crucial to modulate the response to glucocorticoids. Rhinella arenarum is an anuran exhibiting seasonal variations in plasma glucocorticoids and also in the number of binding sites (Bmax) of the testicular cytosolic GR. In this work, we evaluated if the annual pattern of GR protein in the testis varies seasonally and, by an in vitro approach, the role of glucocorticoids, androgens, and melatonin in the regulation of the GR Bmax and protein level. For this purpose, testes were treated with two physiological concentrations of melatonin (40 and 200 pg/ml), with or without luzindole (melatonin‐receptor antagonist); with testosterone, cyanoketone (inhibitor of steroidogenesis) or casodex (androgen‐receptor antagonist); or with dexamethasone or RU486 (GR antagonist). After treatments, Bmax and protein level were determined by the binding of [3 H]dexamethasone and Western blot, respectively. Results showed that GR protein decreases in the winter. The in vitro treatment with melatonin produced a biphasic effect on the Bmax with the lowest concentration decreasing this parameter by a receptor‐mediated mechanism. However, melatonin had no effect on the GR protein level. Conversely, a high concentration of dexamethasone up‐regulated the GR protein and androgens neither changed the Bmax nor the protein level. These findings suggest that seasonal changes in plasma melatonin and glucocorticoids modulate the effect of glucocorticoids in the testis of R. arenarum.